Cyber Counseling Berbasis Nilai Agama sebagai Upaya Mengembangkan Kesehatan Mental Remaja di Era Vuca - Pratama, Beny Dwi; Kadafi, Asroful; Fakhriyani, Diana Vidya; Hariyani, Indaria Tri; Kholidah, Mayya (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2023)
Mental health problems are essential in the VUCA era. Developmental demands in the VUCA era can make individuals anxious and depressed so that it can have an impact on their mental health. In order for individuals to avoid mental health problems, there needs to be a solution to prevent them. In this study, researchers used online counseling (cyber counseling) based on religious values as an effort to develop students’ mental health. The method used in this study is the experimental method, to be precise, the quasi pre-post experiment design. The results of the study show that online counseling (cyber counseling) based on religious values can develop mental health in individuals. Cyber counseling is intended as an alternative virtual counseling model in developing individual mental health and of course mental health as well.